« Queer », « transpédégouine », « torduEs », entre adaptation et réappropriation, les dynamiques de traduction au cœur des créations langagières de l’activisme féministe queer - Marie-Émilie Lorenzi (Glad!)
If queer feminist activists have undoubtedly been able to take up in their own name the slogan “my body is a battleground”, they have also taken decisive steps to invest language itself as a symbolic battleground. Direct action on language and reclamation of hate speeches through distortion are as many counter-discursive strategies that actively contribute to the process of subjectivisation. Language issues thus provide a favorable context to perceive the world and establish comprehensible and safe common grounds to establish oneself as an individual. They fully contribute to the political, cultural and identity production of the queer feminist movement or praxis in France. The aim of this analysis is to investigate the translation dynamics at the heart of language creations achieved by queer feminist activists, especially those which can be related to self-definition issues. Translation is far from being a mere language transcription and raises decisive political and cultural issues. Starting from a contextualised reading and trying to remain as close as possible to its practical uses, the issue here is to point out the ambivalent and complex aspects of any translation process, in perpetual movement between circulation and distortion, reclamation and reconfiguration.